2017
DOI: 10.5137/1019-5149.jtn.19469-16.1
|View full text |Cite
|
Sign up to set email alerts
|

The cervical arteries: an anatomical study with application to avoiding nerve root and spinal cord blood supply

Abstract: Understanding the vascular supply to the cervical spinal cord is important for preventing serious complications such as spinal cord ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…The radiculomedullary artery supplies the spinal cord. Cadaveric studies have demonstrated cervical radicular arteries from the vertebral, ascending cervical, and deep cervical arteries [19]. The C6 radicular artery was larger.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The radiculomedullary artery supplies the spinal cord. Cadaveric studies have demonstrated cervical radicular arteries from the vertebral, ascending cervical, and deep cervical arteries [19]. The C6 radicular artery was larger.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, there has been almost no mention of needle size and safety in the literature. A recent cadaveric study has shown cervical radicular artery calibre to range from 0.75 to 1.02 mm and a case report has shown that these arteries can be inadvertently cannulated with small calibre 25G needles [23,24]. We prefer a larger calibre 22G needle, hypothesising that the larger needle is less likely to inadvertently cannulate small calibre radicular arteries than smaller 25G/26G needles.…”
Section: Discussionmentioning
confidence: 92%
“…The present study also showed that the rate of occlusion by initial EVT was significantly lower in patients with cervical SDAVFs than in those with SDAVFs in other locations (P = 0.04). The reason for the higher rate of incomplete occlusion of cervical SDAVF by initial EVT is thought to be due to the presence of multiple feeders from the PICA in addition to those from the deep cervical artery 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%